LGBT youth in America's schools - Cianciotto, Jason (The University of Michigan Press, 2012)
"Jason Cianciotto and Sean Cahill, experts on lesbian, gay, bisexual, and transgender public policy advocacy, combine an accessible review of social science research with analyses of school practices and local, state, and federal laws that affect LGBT students. In addition, portraits of LGBT youth and their experiences with discrimination at school bring human faces to the issues the authors discuss. This is a ... guide for teachers, school administrators, guidance counselors, and social workers interacting with students on a daily basis; school board members and officials determining school policy; nonprofit advocates and providers of social services to youth; and academic scholars, graduate students, and researchers training the next generation of school administrators and informing future policy and practice"--From publisher's description.